Penerapan Foto Produk Sebagai Optimalisasi Digital Marketing Pada UMKM “Dancuk Jaran” Di Desa Ngadiboyo Kecamatan Rejoso Kabupaten Nganjuk - Hannah Emmanuella Delia; Indah Respati Kusumasari (PT. ALHAFI BERKAH INDONESIA, 2023)
Micro, small and medium enterprises (MSMEs) are important players in economic development and growth in the world, not only in developing countries, but also in developed countries. The development of information technology has changed the scope of the marketing world in recent years. Businesses use the internet as a marketing tool for financial success and to help drive communication with online visibility and sales channels and social media advertising becomes a powerful way to reach various markets for business expansion. Marketing activities that utilize the sophistication of digital technology are often referred to as digital marketing. Interesting content is one of the supporting aspects of digital marketing. The implementation of product photo activities at Dancuk Jaran MSMEs, Ngadiboyo Village is carried out in several stages, starting from conducting field analysis, namely observation and needs, continuing to determine the framework for solving problems. The next process of preparation and execution. The sequence of stages is designed in such a way with the aim of maximizing the photos to be produced to match the message that MSME owners want to convey. Product photo activities were carried out at MSMEs